2017
DOI: 10.1111/jog.13437
|View full text |Cite
|
Sign up to set email alerts
|

Myoma and myomectomy: Poor evidence concern in pregnancy

Abstract: Aim: Summarize the results of the many, but often underpowered, studies on pregnancy complicated by myoma or myomectomy. Methods: Survey of the electronic PubMed database for the last two decades was conducted. We selected reviews, meta-analyses, case series, case reports, clinical studies only with statistical analysis, and guidelines from scientific societies. Results: Delaying childbearing leads to an increased incidence of pregnancy complicated by fibroids or previous myomectomy. Approximately 10-30% of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
1
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 116 publications
1
96
1
20
Order By: Relevance
“…Previous studies have also reported increased adverse pregnancy outcomes, including abnormal placentation, such as placenta previa or placenta accreta, [10][11][12] preterm delivery, cesarean delivery, uterine rupture, and postpartum bleeding, in women with a history of myomectomy. [13][14][15][16] The true incidence of uterine rupture during subsequent pregnancy following myomectomy is di cult to establish, because most of the studies have been cases, case series, or small retrospective cohort studies that do not account for the total number of pregnancies achieved after myomectomy and their consequent outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have also reported increased adverse pregnancy outcomes, including abnormal placentation, such as placenta previa or placenta accreta, [10][11][12] preterm delivery, cesarean delivery, uterine rupture, and postpartum bleeding, in women with a history of myomectomy. [13][14][15][16] The true incidence of uterine rupture during subsequent pregnancy following myomectomy is di cult to establish, because most of the studies have been cases, case series, or small retrospective cohort studies that do not account for the total number of pregnancies achieved after myomectomy and their consequent outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…There have been poor evidences about obstetric outcomes in women with myoma and previous myomectomy. 10 The purpose of this study was to evaluate adverse pregnancy outcomes in women with a history of diagnosed myoma or myomectomy, including prevalence of uterine rupture in women with myomectomy, according to the time interval after myomectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of uterine myomas in pregnancy varies from 1.6% to 12.6% with higher prevalence in elderly pregnant women or women undergoing in vitro fertilization. [7][8][9][10][11] They are commonly seen in African-American women with an incidence of 18% followed by 8% in white women and 10% in Hispanic women. 10 They are more common in primigravida over 35 years of age due to responsive growth to ovarian steroid hormones, estrogen and progesterone and are rarely seen before puberty.…”
Section: Myomas In Pregnancymentioning
confidence: 99%
“…[7][8][9][10][11] They are commonly seen in African-American women with an incidence of 18% followed by 8% in white women and 10% in Hispanic women. 10 They are more common in primigravida over 35 years of age due to responsive growth to ovarian steroid hormones, estrogen and progesterone and are rarely seen before puberty. 1,2 On physical examination around 42% of large fibroids (>5 cm) and 12.5% of smaller fibroids can be diagnosed.…”
Section: Myomas In Pregnancymentioning
confidence: 99%
“…Surgical myomectomy prolongs the time till birth as the patient requires adequate postsurgical healing. Besides, all patients after surgical myomectomy should be treated as high-risk of obstetric complications in case of a future pregnancy [48]. Furthermore, all kinds of UF surgeries, even minimally invasive methods, are procedures that could irreversibly change or injure the pelvic cavity and cause pelvic adhesions, which in turn might reduce further reproductive potential [49].…”
mentioning
confidence: 99%